Perbandingan Konsep Kesejahteraan Antara Persfektif Islam dan Barat - Muhammad Yassir Fahmi; Lusiana Handayani; Aneta Rakhmawati (Indonesian Journal of Applied Accounting and Finance, 2025)
The difference in worldview and scientific methods between Western and Islamic scholars results in differences in explaining the concept of welfare and the practices to achieve it. This study aims to explain the differences in the concept of welfare between the Western and Islamic perspectives using a systematic literature review method. Based on the research results, it was found that the concept of welfare is born from theories about human needs. Muslim scholars differ from Western scholars in explaining the theory of human needs, namely by making religion the primary and priority need in human life. Therefore, the concept of welfare from the Islamic perspective is the fulfillment of human needs, both material and spiritual aspects, to obtain happiness in this world and the hereafter. Meanwhile, Western scholars negate religion as an important and priority aspect in fulfilling human needs. Thus, the concept of welfare from the Western perspective is understood as the fulfillment of material and non-material needs, but it does not bring human happiness. The difference in the concept of welfare between the two also gives rise to differences in economic ethics. The concept of welfare from the Islamic perspective will make society practice economics with values, ethics, and morals (akhlak mahmudah). Conversely, the concept of welfare from the Western perspective will make utilitarianism the ethic in economics. The ethics of utilitarianism views that morality is determined by the consequences of human behavior.